Plant layout design using the ProModel program to optimize spaces and minimize times in a retreading company in Cajamarca - Quispe Vásquez, Luis Roberto; Gonzales Abanto, Wilson Alcides; Correa Llanos, Dereck Guiampierre; Uriarte Valdivia, Jhoana Andrea; Valencia Rodas, Andrea Alessandra (LACCEI, 2024)
Plant layout is the process of organizing the physical elements of a company to maximize efficiency and productivity. In the case of retreading companies, a good plant layout can help reduce production times, operating costs and errors. Plant layout is a discipline of industrial engineering that involves work techniques, evaluation and Planning the distribution of elements in a plant to improve production, productivity and reduce costs, this is an important tool for companies of all sizes and sectors. In the case of the retreading company in which the research will be carried out, a good plant layout can help improve efficiency and productivity. The main objective of the research is to increase productivity with a plant distribution proposal, reduce operation times and increase profits in a planned way, for which what was learned in systems simulation was considered, in which in the present The research used the ProModel simulator, which when applied, the plant layout was analyzed and improved, thus obtaining satisfactory and efficient results for the retreading company, which was reflected in its profits.